Characterization of antioxidant activity of sulfur compounds in black garlic - Wang, Wei-dong; Sun, Yue-E; Chen, Hong-wei (Cellular and Molecular Biology, 2018)
Different types of sulfur compounds, namely S-allyl-L-cysteine (SAC), S-allyl-L-cysteine sulfoxide (ACSO) and a synthetic Î³-L-glutamyl-S-allyl-L-cysteine (GSAC) were extracted from black garlic and their inhibition to the advanced glycation end-products (AGEs) were investigated. Upon addition of inhibitor, the amount of produced fructosamine was determined by UV visible spectroscopy. The change of pentosidine and fluorescent AGEs during reaction was detected by fluorescence method and the change of carboxymethyl lysine (CML) was detected by high performance liquid chromatography. It was found that the inhibitory effects of SAC and ACSO are stronger to the early and mid non-fluorescent products in glycosylation reaction, and GSAC has an obvious inhibitory effect on the later reaction products. All these three inhibitors can effectively inhibit advanced glycation reaction. Although their effects on glycation products are different due to different chemical structures, they have similar inhibitory effects on fluorescent products.